2021
DOI: 10.1038/s41598-021-96694-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of protein from Bombay locusts and its impact on functional and antioxidative properties

Abstract: Impact of ultrasound-assisted process (UAP) on yield, functional properties, antioxidant properties and molecular characteristics of protein extracted from Bombay locusts (BL) (Patanga succinta L.) was studied. Different conditions of UAP were implemented for different amplitudes (40–60%) and times (10–30 min) during aqueous extraction. Notably, UAP could enhance yield and protein recovery, compared with those from typical process (TP) (continuously stirred at 100 rpm at room temperature for 1 h). UAP conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 54 publications
3
37
1
Order By: Relevance
“…An experiment was completed to extract protein from Bombay locusts by implementing ultrasound-assisted extraction. The protein yield from the ultrasound-assisted extraction was significantly higher compared to the typical conventional extraction [89]. This foresees the prospective of LBS integrated with ultrasound-assisted extraction for the recovery of protein as appealing and worthy of further research.…”
Section: Integration Of Lbs With Other Technologiesmentioning
confidence: 78%
“…An experiment was completed to extract protein from Bombay locusts by implementing ultrasound-assisted extraction. The protein yield from the ultrasound-assisted extraction was significantly higher compared to the typical conventional extraction [89]. This foresees the prospective of LBS integrated with ultrasound-assisted extraction for the recovery of protein as appealing and worthy of further research.…”
Section: Integration Of Lbs With Other Technologiesmentioning
confidence: 78%
“…These differences in the protein yielding when using PUP may be due to the extraction conditions, the type of ultrasound device and configuration (bath or piezoelectric sonotrode), surface area of the pre-treated samples, residual fat percentage of the powder, and the presence of chitin in the case of Orthoptera ( Choi et al, 2017a ). Moreover, because of the high energy addition to the protein molecules due to ultrasound application, variations on the protein recovery are also attributed to changes in the surface hydrophobicity of proteins, due to splitting and fractionation of the protein structure due to the cavitation phenomenon, which leads to changes in the conformation of the secondary, tertiary, and quaternary structures of the protein, affecting the functional properties such as the solubility ( Kingwascharapong et al, 2021 ). In this sense, proteins in their native state usually perform as aggregates with low dispersibility in aqueous media, but when ultrasound is applied, a large number of cavitation bubbles are produced, which cause a rapid increase in local temperature and pressure at the neiborhood of the collapsing bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…UAP disrupts the non-covalent bonds of the skin matrices and exposes hydrophobic amino acid residues [30] . Kingwascharapong et al [31] found that the hydrophobic content of insect proteins could be induced by ultrasound treatment, where a longer ultrasonication time resulted in higher H 0 ANS. Conversely, a decrease in the hydrophobic content of proteins could occur with excessive energy from ultrasound treatment due to protein aggregation via protein–protein interactions [9] , [31] .…”
Section: Resultsmentioning
confidence: 99%